Economic analysis of intravenous immunoglobulin and plasma exchange therapies for the treatment of Guillain-Barré Syndrome in a university-based hospital in the South of Brazil - Brito, Alexandre Paulo Machado de; Ferreira, Maria Angélica Pires; Maciel, Paola Panazzolo; Moreira, Leila Beltrami (Clinical and Biomedical Research, 2011)
Introduction: Direct costs for treating Guillain-Barré Syndrome (GBS) represent a significant financial burden to public hospitals. Few studies compared the cost of plasma exchange (PE) treatment with human intravenous immunoglobulin (IVIg). Objectives: To compare the cost of two therapies for GBS: IVIg and PE. Secondary objective was to evaluate compliance to IVIg prescription guidelines of the Pharmacy and Therapeutics Committee (PTC). Methods: A cross-sectional study included 25 patients with GBS admitted in a university affiliated hospital from June, 2003 through June, 2008. The costs of IVIg (n=20) and PE (n=5) were evaluated through the cost minimization method, considering direct medical costs yield by the management of the institution. Patients receiving treatments other than PE or IVIg were excluded. Data were collected by medical records review. Clinical endpoint was disability on discharge, established by the 7-point scale of Hughes. Compliance to the PTC guidelines was evaluated considering the dose and prescription regime of IVIg. Results: Twenty-five participants, ranging from 2 to 70 years of age, were included. No difference occurred in any medical variables related to the treatment or in the main clinical outcome measured by the Hughes’ scale. The mean direct cost of PE treatment was US 6,059± 1,701 per patient, and the same expense for IVIg was US 18,344±12,259 (P = 0.035). Total inpatient cost was US 25,730± 18,714 in the PE group, and 34,768± 27,766 (p=0.530) in the IVIg group. Conclusions: In a university-based hospital, PE is equally effective and less expensive than IVIg to treat GBS.